2009
DOI: 10.1016/j.ajog.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational factors and risk of preterm birth in nurses

Abstract: Objective We evaluated the risk of first-trimester exposures among nurses and the risk of preterm birth among participants of the Nurses’ Health Study II. Study Design Log binomial regression was used to estimate the relative risk (RR) for preterm birth in relation to occupational risk factors, adjusting for age, parity, work schedule, physical factors, and exposures to chemicals and x-rays. Results Part-time work (<= 20 hours a week) was associated with a lower risk for preterm birth [RR=0.7, 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 39 publications
1
74
1
10
Order By: Relevance
“…These results contradict most of the previous studies where unfavorable effects among nurses were observed, often in relation with specific exposures (15,20,(27)(28)(29); only one study conducted in Canada showed a lower risk of low birth weight infants among nurses (30). Nurses Figure 2.…”
Section: Casas Et Alcontrasting
confidence: 56%
“…These results contradict most of the previous studies where unfavorable effects among nurses were observed, often in relation with specific exposures (15,20,(27)(28)(29); only one study conducted in Canada showed a lower risk of low birth weight infants among nurses (30). Nurses Figure 2.…”
Section: Casas Et Alcontrasting
confidence: 56%
“…32 Our findings regarding exposure to sterilizing agents is consistent with our previously reported association of sterilizing agents with risk of preterm birth (RR=1.9, 95% CI = 1.1-3.4). 33 Glutaraldehyde, formaldehyde, ethylene oxide, orthophthalaldehyde, peracetic acid, and hydrogen peroxide are used to disinfect medical equipment and surgical instruments. Ethylene oxide and formaldehyde are recognized as carcinogenic and mutagenic, but there have been few studies in humans to evaluate their reproductive toxicity, 3,34,35 and most had limited sample sizes.…”
Section: Commentmentioning
confidence: 99%
“…[76][77][78][79][80][81][82] Diğer taraftan pek çok gözlemsel çalışma ve bir randomize araştırmada, preterm doğum ile iş veya egzersiz arasında ilişki olmadığı, varsa da çok az bir ilişki olduğu bildirilmiştir. 83,84 Hatta bazı çalışma-larda, aktiviteye harcanan zaman arttıkca preterm doğum riskinde azalma olduğu bildirilmiştir. 84,85 Özetle, gebelik sırasında düzenli egzersize devam eden kadınlarda preterm doğum riskinin düşük ol- …”
Section: -72unclassified
“…Turkiye Klinikleri J Gynecol Obst 2017;27(2): [79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] mekanizma üzerinden erken doğum eylemi ve hipoalbuminemi birlikteliği de yayımlanmıştır. 147 …”
Section: Albuminunclassified